The role of bukatsu or club activities in the socialization process of young people in Japan - Muhametrahimova А Т; Zhanuzakov, A A (Journal of Oriental Studies, 2016)
The phenomenon of social integration is of paramount importance in the study of the transformation processes of the youth in the modern period of radical technological, informational and social changes in Japan and the world in general. This article discusses the role of club activities in the socialization process of young people in secondary schools and higher education institutions in Japan.